Effect Of Intraoperative Erector Spinae Block For Faster Recovery And Reduced Post-Operative Pain In Patients Undergoing Discectomies & Spinal Decompression - Azizi, Arham; Siddiqui, Athar Muniruddin; Munshi, Naseem; Masroor, Muhammad Salman; Salahuddin, Zahra; Hassan, Muhammad (Journal of Rawalpindi Medical College, 2024)
Objective: To evaluate the efficacy of intraoperative Erector Spinae Block (ESB) in reducing postoperative pain and facilitating recovery in patients undergoing spinal surgeries. Methods: A prospective cohort study was conducted at the Orthopedic Department of Dr. Ziauddin Hospital Karachi, Pakistan from 15th June 2022 to March 31st, 2023. Patients aged 30 to 50 years undergoing spinal surgeries such as discectomies and spinal decompressions with ASA status I or II were included in the study. Participants were divided into two groups: those receiving ESB (n=33) and a control group receiving standard pain management (n=33). The primary outcome measured was the intensity of postoperative pain, assessed using the Visual Analog Scale (VAS) at 6 hours, 12 hours, and 24 hours post-surgery. Secondary outcomes were the length of hospital stay and the presence of nausea and vomiting. Results: Significant reductions in pain scores were observed in the ESB group compared to the control group at 6 hours (median scores: 5 vs. 7, p=0.003), 12 hours (5 vs. 6, p=0.028), and 24 hours (3 vs. 4, p=0.038) post-intervention. The ESB group had a shorter median hospital stay (2 days) compared to the control group (3 days), with this difference being statistically significant (p=0.001). Conclusion: ESB is an effective and safe technique for managing postoperative pain in spinal surgery patients. It offers significant benefits over traditional pain management approaches, including reduced pain scores, lower opioid consumption, and shorter hospital stays.